Application of Graph Coloring on Nurse Work Scheduling at H. Adam Malik Hospital Medan Using the Tabu Search Algorithm - Ananda, Rizky; Indra, Zulfahmi; Nasution, Hamidah (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
Complex problems that usually occur in every hospital, one of which is scheduling with so many aspects, for example: the number of nurses, the distribution of nurse shifts, time off or leave and others. With the manual method that is still used in compiling the nurse's work schedule, it makes it difficult for an irregular and regular schedule. In solving the scheduling problem, the graph coloring method can be used. This scheduling problem can be solved by graph coloring. One solution to solve the problem of concluding graphs in scheduling is the Tabu Search Algorithm. A method that works as an effective problem solving method in finding the best solution to a problem. A method is used to solve the problem by making a representation in the form of a graph where the nurse is a node and grouping nurses as an edge by implementing the graph coloring into the Tabu Search Algorithm.